PENGARUH SUMBER INFORMASI TERHADAP KEPUTUSAN ADOPSI INOVASI PERTANIAN BIOINDUSTRI SERAI WANGI- TERNAK - Rushendi Rushendi (Perpustakaan Nasional RI, 2017)
The innovation of bioindustry agriculture is expected to improve the knowledge, attitudes and skills of farmers through the information sources that will ultimately increase the incomes and welfare of the farmers. The application of technological innovation by farmers is affected by factor of individual potential in implementing innovation, the role of information sources in providing and disseminating innovation, and also external factors which allow the users to apply technological innovation. The application of innovation is also determined by the nature of the innovation itself. The availability of information, the credibility of information sources and the means of access to information will determine the effect of innovation adoption decision. The purpose of this study is to find out the effect of information sources obtained by farmers on innovation adoption decision of bioindustry agriculture of citronella - cattle. The study used survey method with descriptive quantitative approach with ,regression correlation test. The locations of study were selected purposively with cluster random sampling technique in 4 hamlets of Cikahuripan Village in Lembang District, in March-May 2016, with the num ber of farmers was 230. The results showed that the components of innovation adopted by farmers are cultivation of citronella, utilization of livestock waste into organic fertilizer, utilization of livestock waste into biogas for households, and production of yoghurt. Factors affecting innovation adoption decision of bioindustry agriculture of itronella- cattle are communication through dialogue, the validity of information and the competence level of informants.